On the fallacy of neglecting firm size in assessing export marketing strategies - Harald Trabold (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
Empirical evidence from French exporters presented in this paper shows that the vast majority of firms follow a strategy of market concentration when market numbers or a combination of market numbers and the share of the key markets is used as an indicator. These results are at odds with many other studies on the subject. The main reason for this is the size distribution of exporters which corresponds to Gibrat's law. In addition, industry effects and the stage of internationalisation were also found to affect the number of export markets. Given the fact that only large exporters can afford to penetrate a large number of markets and that micro-, small-, and medium-size firms constitute the majority of exporters the use of a uniform number of markets as a dividing line will automatically categorise most firms as following a strategy of market concentration. Future research on export marketing strategies should therefore be conducted with firms of similar size, the same industry and the same stage of the internationalisation process.
Keywords: 330; Internationales Marketing; Internationale Betriebswirtschaftslehre; Betriebsgröße; Frankreich